Perancangan Sistem Keamanan Perumahan Menggunakan Face Recognition Berbasis Android - Hidayatullah, Ari; Putra, Yustian Adhi (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Environmental security is an important issue that must be considered, relying on the physical strength of security officers to stand guard 24 hours is not enough, an information and communication technology-based system is needed to assist security officers and neighborhood residents in monitoring the environment and its surroundings from possible disturbances of good crime. from outside as well as from within the environment itself. Based on these environmental security issues, the authors were inspired to design a residential security system application using the face recognition method. The main objective of this research is to help the environmental security system in housing. Data collection methods used are interviews, observation and literature study. The results of this study are residential security system applications using Android-based face recognition. This residential security system application is designed with simple systems and features to make it easier for the user. The Face Recognition method makes it easier for security officers to carry out their duties to recognize people who enter and leave housing. This security system application is designed to help residential residents, especially security officers, to be able to detect known and unknown people in housing.